Cadmium modulates NADPH oxidase activity and expression in sunflower leaves - Groppa, María Daniela (2012)
The production of reactive oxygen species (ROS) and the ways by which ROS are generated are very important facts related to heavy metal toxicity in plants. In this work, superoxide anion (O2·-) generation diminished in cadmium treated sunflower (Helianthus annuus L.) leaf discs, and this reduction was time and Cd-concentration dependent. In line with these findings, we observed that NADPH-dependent oxidase activity was significantly inhibited by 0. 1 and 0. 5 mM Cd2+ treatments and the expression of the NADPH oxidase putative gene related to O2·- synthesis in sunflower leaves was 83 % inhibited by 0. 1 mM CdCl2 and almost completely depleted by 0. 5 mM CdCl2. © 2012 Springer Science+Business Media B.V.